Zad.1
Podane wyrażenia zapisz w najprostrzej postaci.
a)(x+1) do potegi 2 - x do potegi 2 +2 =
b) ( a-2) do potegi 2 +4-a do potegi 2 =
c)(x+4)do potegi 2 + (x-4) do potegi 2 =
d) ( 2a - 1) do potegi 2 - (2a+1) do potegi 2 =

Zad.2
Rozwiarz nierownosci i przedstaw je na osi liczbowej.

a)(x-3) do potęgi 2 < x(x-2) - x =
b)(3-x )do potęgi 2 > 2 - x(6-x) =

Dzięki :**

2

Odpowiedzi

2009-11-26T15:37:38+01:00
A)
(x+1)² - x² + 2 = x²+1-x²+2 = 3
b)
(a-2)²+ 4 -a² = a²- 4 + 4 a²= 2a²
c)
(x+4)² + (x-4)² = x² + 16 + x² - 16 = 2x²
d)
( 2a - 1)² - ( 2a + 1)² = 4a²-1 - 4a² - 1 = -2

a)(x-3)²< x(x-2) - x
x² + 9 < x² - 2x - x
x² - x² +2x + x < -9
3x < -9 | :3
x <-3



B)(3-x )²> 2 - x(6-x)
9 - x² > 2 - 6x -x²
-x² +x² +6x > 2-9
6x > 7 | :6
x > 7/6

2009-11-26T15:48:17+01:00
Zad1.
a)(x+1) do potegi - x do potegi 2 +2 = xdo potegi 2 +1 _ xdo potegi 2 +2 = 3
b) ( a-2) do potegi 2 +4-a do potegi 2 =a do potegi 2 - 4 + 16 = a do potegi 2 + 12
c)(x+4)do potegi 2 + (x-4) do potegi 2 = x do potegi 2 + 16 + x do potegi 2 - 16 = 2x do potegi 2
d) ( 2a - 1) do potegi 2 - (2a+1) do potegi 2 = 0

Zad.2
Rozwiarz nierownosci i przedstaw je na osi liczbowej.

a)(x-3) do potęgi 2 < x(x-2) - x
x Zad.2
Rozwiarz nierownosci i przedstaw je na osi liczbowej.

a)(x-3) do potęgi 2 < x(x-2) - x
x do potęgi 2 - 9 < x do potęgi 2 - 2x - x
-9 < x do potęgi 2 - 2x - x - x do potęgi 2
-9 < -3x /:(-3)
3 > x

b)(3-x )do potęgi 2 > 2 - x(6-x) =
9 + x do potęgi 2 > 2 - 6x +x do potęgi 2
9 - 7 > 2 - 6x + x do potęgi 2
7 > 6x /:7
x = 7/6